The Effect of Cerastoderma lamarcki and Rice Bran Extract on Wharton\'s Jelly-Derived Mesenchymal Stem Cells Differentiation - Fariba Nosrati; Homa MohseniKouchesfahani; Mohammad Nabiuni; Latifeh Karimzadeh; Fereshteh Dorazehi (Fasa University of Medical Sciences, 2021)
Background & Objective: Nowadays, the use of natural materials in regenerative medicine is very important, especially using substances with calcium carbonate structure due to their similarity to the bone structure. In this study, the effect of Cerastoderma lamarcki shell and rice bran extract on stem cell proliferation and differentiation has been investigated. Materials & Methods: First, crastoderma shells were collected and cut into small pieces. Its compounds were analyzed by X-ray diffraction. Finally, the structural features of shells were investigated by SEM. Stem cells were extracted and cultured from the umbilical cord of Wharton's jelly. After cells seeding on the scaffold, cell survival was studied by MTT. Adhesion, morphology, and diffusion of cells on the shells were also examined by SEM. Cells were stimulated by osteogenic medium and osteoblastic differentiation by alkaline phosphatase activity was studied. Rice bran ethanolic extract was used. Cell survival was studied by MTT technique and osteogenic differentiation was studied by Alizarin Red staining. Results: MTT studies showed appropriate adhesion of cells on the scaffold and SEM studies also showed successful binding and their appropriate morphology on the scaffold. Alkaline phosphatase studies showed that osteogenic differentiation of cells on shells is significant. In another part of this study, we studied the survival and osteogenic differentiation of these cells in treatment with ethanolic extract of rice bran. MTT studies showed a dose-dependent decrease in cell survival in the presence of the extract. Alizarin staining also showed the differentiation potential of this substance. Conclusion: The results showed the appropriate potential of these two natural substances in bone differentiation. However, further studies are needed to prove their effects.